Superovulatory response, production and quality of embryos of cows fed on linseed or canola seed supplemented diets - Karina Perehouskei Albuquerque (Acta Scientiarum. Animal Sciences, 2012)
Superovulatory response, production and embryo quality and the effects of seasonal changes on embryo production of Nellore cows fed on either linseed (n-3) or canola seeds (n-6) were evaluated. Sixteen Nellore cows (550 ± 48.0 kg) were fed on three diets: control diet (CON), diet with linseed (LIN) and diet with canola seed (CAN) during four seasons. There was no difference in superovulatory response and in total corpora lutea produced when diets are taken into consideration. The number of cows that responded to superovulatory treatment was higher in the winter (93.8%) than in the summer (62.5%). No difference with regard to the three diets existed on the average number of total structures (6.20, 4.96 and 6.50), unfertilized structures (2.53, 1.17 and 1.60) or congealable embryos (3.40, 1.30 and 3.80). Average degenerated embryos were higher for cows fed on LIN diet (2.48) than for those fed on CON diet (0.32); the CAN diet presented an intermediate response (1.10). Mean total structures produced were lower during the winter (3.57) and summer (3.50) than during the autumn (8.75) and spring (7.25).